The Relevance of The Concept of Islamic Education Reform Fazlur Rahman's Perspective with The Context of The Development of The Current Era - Lathifah, Dwi Nur Istianah (Jurnal Sosial Teknologi, 2025)
The decline of Islamic intellectualism post-colonialism and the persistent dichotomy between religious and secular education underscore the urgency of reforming Islamic education. Fazlur Rahman's Neo-Modernist approach, advocating integration, remains influential yet under-explored empirically. This study examines the relevance of Rahman's model in contemporary Indonesia, focusing on its application in pesantren and modern schools, and evaluates bilingualism and technology as modern tools for integration. A qualitative descriptive-analytic method is employed, analyzing primary texts (Rahman’s works) and secondary data (previous studies, articles), supplemented by field observations in selected institutions. Rahman’s integration model shows promise in reducing educational dualism but faces implementation barriers, such as resource disparities and conservative resistance. Bilingual education and ethical technology are viable enhancers of critical thinking and unity. The study offers practical strategies for policymakers and educators to modernize Islamic education while preserving its moral core, bridging historical divides for a holistic system.